Motor abnormalities and basal ganglia in schizophrenia: evidence from structural magnetic resonance imaging - Hirjak, Dusan; Wolf, Robert Christian; Wilder-Smith, Einar; Kubera, Katharina Maria; Thomann, Philipp (Brain topography, 2015)
At the beginning of the twentieth century, many authors proposed that a considerable number of schizophrenic patients experience genuine motor abnormalities (GMA). In the era of antipsychotic treatment, GMA became a scientifically and clinically challenging characteristic of schizophrenia. Over the past 10 years, several magnetic resonance imaging (MRI) studies suggested a crucial role of the motor system in this disorder. Constituting a major relay center in the extrapyramidal motor system and being involved in the automatic execution of motor plans, an involvement of the basal ganglia with GMA and schizophrenia is plausible. However, the precise morphological correlates of GMA have remained controversial. The aim of this paper is to systematically review structural neuroimaging findings on GMA and basal ganglia in individuals with schizophrenia. Nineteen structural MRI studies were identified for inclusion in the review. Considering the extant data, there is some evidence for volumetric and shape alterations of basal ganglia in schizophrenia being in part determined by psychopathology and GMA, and not entirely explained by antipsychotic medication effects.
Published online: 31 May 2014
Gesehen am 03.09.2020